놀이치료자의 자기효능감과 역전이 관리능력의 관계에서 스트레스 대처방식의 매개효과 - 윤선재; Son Jai Youn; 이영애; Young Ae Lee (한국놀이치료학회지(놀이치료연구), 2012)
본 연구는 놀이치료자의 개인적 특성인 자기효능감이 스트레스 대처방식을 거쳐 역전이 관리능력에 미치는 직 간접 효과를 알아보고자 하였다. 이를 위해 서울 및 경기, 충남 지역의 놀이치료자 139명을 대상으로 놀이치료자 자기효능감 척도(COSE: Counseling Self-Estimate Inventory), 스트레스 대처방식(The Ways of Coping Checklist), 역전이 관리능력(CFI: Countertransference Factors Inventory)척도를 사용하였다. 자료분석을 위해 SAS 8.2 통계 프로그램을 사용하여 상관분석, 단순회귀분석, 중다회귀분석을 실시하였고, AMOS 18 통계 프로그램에 의한 구조방정식 분석을 실시하였다. 본 연구의 결과는 다음과 같다. 첫째, 자기효능감이 높은 치료자일수록 역전이 관리능력이 뛰어나며, 특히 공감능력이 좋은 것으로 나타났다. 둘째, 스트레스 대처방식 중 문제 중심 대처를 하는 놀이치료자들일수록 역전이 관리능력이 높고, 문제 중심 대처를 많이 사용하고 소망적 사고 대처를 적게 사용하는 놀이치료자들일수록 불안을 관리하는 능력이 높은 것으로 나타났다. 셋째, 놀이치료자의 자기효능감이 높을수록 문제 중심 대처를 사용하고, 역전이 관리능력 또한 높은 것으로 나타났을 뿐 아니라 놀이치료자가 문제 중심 대처를 사용할 때 역전이 관리능력이 높은 것으로 나타났다. 또한 놀이치료자의 자기효능감은 문제 중심 대처를 거쳐 역전이 관리능력에 정적인 직 간접 영향을 미치는 것으로 나타났다. This study was conducted in order to research how the self-efficacy of play therapists impacts upon the counter- transference management abilities directly or indirectly on ways to cope with stress. The subjects comprised 139 play therapists who have conducted play therapy sessions in Seoul and its metropolitan area. For the purposes of this research, Counseling Self-Estimate Inventory, The Ways of Coping Checklist and Counter-transference Factors Inventory were used. The data collected in this study was analyzed by means of the SAS 8.2 statistical program with Pearson`s correlation analysis, simple regression analysis and multiple regression analysis. In addition structural equation analysis was carried out using the AMOS statistical program. The results of this study can be summarized as follows. First, it was revealed that play therapist`s self-efficacy influenced on each sub-factor of the counter-transference management ability, Second, it was found that the ability to cope with stress by play therapists had an effect on counter-transference management abilities, The results of structural equation verification the effects, both directly or indirectly, on self-efficacy of play therapists and on their counter-transference management abilities through problem-oriented coping strategies.